The Impact of a High-Fat Diet on Blood Glucose Levels - Atta Celine Nouli Saruksuk; Jekson Martiar Siahaan; Irene Ruminta Tua Damanik; Endy Juli Anto; Jadeny Sinarta (Jurnal Kedokteran Methodist, 2024)
Background: Diabetes mellitus (DM) sufferers in the world and even inIndonesia are expected to continue to increase, especially type 2 DM(DMT2). DMT2 often occurs in people who are obese, the cause of obesityis often consuming foods that contain a lot of fat. Hyperlipidemia plays arole in the pathogenesis of pancreatic β-cell dysfunction.Research method: This study is an experimental laboratory study with apretest-posttest only controlled group design, using male white rats(Rattus norvegicus) with a sample size of 30 divided into 6 groups, namelythe normal group, the negative control group, the positive control group,the group given a high fatty diet (HFD). The independent variable is HFD,while the dependent variable is blood sugar levels. Data were analyzedusing the Anova test.Results: Giving HFD of 4 ml/day for 4 weeks has not been able to increaseKGD to hyperglycemic, this is thought to be because the HFD was notgiven for long enough so that insulin resistance had not occurred in thetest animals.Conclusion: Based on the results of the study, it was concluded that givingHFD for 4 weeks still could not increase KGD in male white mice tobecome hyperglycemic